Proceedings of the Workshop on the use of Solar Energy for the Cooling of Buildings - Workshop on the use of Solar Energy for the Cooling of Buildings (2nd : 1975 : University of California, Los Angeles); de Winter, J. W.; de Winter, Francis; United States. Energy Research and Development Administration. Division of Technical Information (Springfield, Va. : N.T.I.S., 1976)
03